2016
DOI: 10.5098/hmt.7.32
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady flow and heat transfer of UCM fluid in a porous channel with variable thermal conductivity and ion slip effects

Abstract: This article presents an unsteady incompressible Upper Convected Maxwell (UCM) fluid flow with temperature dependent thermal conductivity between parallel porous plates which are maintained at different temperatures varying periodically with time. Assume that there is a periodic suction and injection at the upper and lower plates respectively. The governing partial differential equations are reduced to non linear ordinary differential equations by using similarity transformations and the solution is obtained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In both the expanding and squeezing cases the axial velocity has a decreasing effect till a certain point and then the elastic forces dominate the viscous effects to have higher velocity towards the boundaries. Choi et al [41] observed the similar behavior of viscoelastic effects in the flow of UCM fluid through permeable channels. He explained that after a point the viscous forces are dominated by the elastic forces for low Reynolds numbers.…”
Section: Effect On Flowmentioning
confidence: 67%
See 1 more Smart Citation
“…In both the expanding and squeezing cases the axial velocity has a decreasing effect till a certain point and then the elastic forces dominate the viscous effects to have higher velocity towards the boundaries. Choi et al [41] observed the similar behavior of viscoelastic effects in the flow of UCM fluid through permeable channels. He explained that after a point the viscous forces are dominated by the elastic forces for low Reynolds numbers.…”
Section: Effect On Flowmentioning
confidence: 67%
“…Mahantesh et al studied the three dimensional flow of Casson nanofluid over Among these models, upper convected (UC) Maxwell fluid is a popular one as this approximation is close to the physical reality and very less mathematical complications compared to the other stress formulations [34]. Several authors [35][36][37][38][39][40][41][42][43][44][45] have studied the effects of magnetic field, porous medium on the flow of UC Maxwell fluid over stretching sheets and porous channels. Their observations show that the velocity profiles are deeply affected by the presence of this upper convected derivative and show deviation from the Newtonian case.…”
Section: Introductionmentioning
confidence: 99%
“…On the vertical stretching sheet, the thermal buoyancy and variable thermal conductivity with heat source is studied by Abel et al (2009). Ojjela et al (2016) studied the varying thermal conductivity impact on UCM fluid. Rangi and Ahmad (2012) analyzed the boundary layer flow past a stretching cylinder and heat transfer with variable thermal conductivity.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%